Characterization of Car Wash Wastewater from Manually dispersed, Snow and Auto Car Wash Stations - Shahrul Shafendy Bin Ibrahim, Muhammad; Haslina Hashim, Nor (International Journal of Engineering and Technology, 2018)
Although commonly perceived lightly in the eye of public, car wash wastewater should be taken more seriously as they have the tendency to be harmful and toxic not only towards the environment, but also humans. In this study, car wash wastewater samples were taken from three stations in Johor with different cleaning methods; manually-dispersed car wash (MCW), snow car wash (SCW) and auto car wash (ACW). At each station, samples were taken during the initial rinsing (IR), and final rinsing (FR) of the vehicles. The samples taken were analyzed for its pH, chemical oxygen demand (COD), biological oxygen demand (BOD), oil and grease (O&G), total suspended solids (TSS), anions (anionic surfactant, nitrate, sulphate, chloride, fluoride, orthophosphate) and heavy metals (iron, zinc, magnesium, chromium, manganese, copper, lead, silver). The results obtained shows that there appears to be no specific pattern to differentiate between the IR and FR samples due to the different washing methods, chemicals and equipment used. The level of contamination of the car wash wastewater was SCW>MCW>ACW. Overall, the result shows that some of the samples did not pass the standard discharge limit; pH, COD, BOD, O&G, TSS, AS and Fe. This shows that car wash wastewater produced in the cleaning activities should be given more concern and need to be treated before being released to the water body.Â Â